Charcot Ankle Deformity: Can the Limb be Salvaged?. Issue 4 (November 2022) - Aminian, Arash; Choi, Daniel; Saghaeidehkordi, Jalal; Black, James; Lee, David; Harris, Thomas G.
Category: Diabetes; Ankle Introduction/Purpose: Diabetes mellitus (DM) may result in Charcot arthropathy (CA) in 0.1% to 2.5% of diabetic patients. Complications may arise including joint dislocation, deformities, ulcerations, and limb amputation. Surgical intervention has been shown to improve patient's walking ability and health-related quality of life compared to use of orthotics in addition to reduction of ulcer, bone infection, use of orthoses, and amputation. A retrospective review of patients with ankle charcot arthropathy was performed with hindfoot nail fixation. The aim of the study was to determine radiographic healing, complication rates of surgical intervention, and patients' ability to ambulate with therapeutic inserts or boots. The results obtained from this study serve to provide evidence for intervention via operative fixation and limb salvage in this cohort of patients. Methods: A retrospective review of patients treated with hindfoot nail with CA of the ankle was performed between 2016 to 2022. The demographic data, BMI, cause of the charcot arthropathy, the pre-operative radiographic deformity, and prior wounds and infection data was recorded. We identified 18 consecutive patients that underwent surgical intervention. The surgical technique included bimalleolar exposure, correction of the deformity, hindfoot fusion nail with or without structural femoral head graft. The follow up data collected included post-operative complications, radiographic evaluation of union, and clinical data on type of shoe wear or boots used for ambulation. Results: We identified 17 consecutive patients undergoing hindfoot deformity correction with hindfoot nail. The average follow- up for the patients was 1.7 year. The cause of neuropathy was diabetes in 15 patient and idiopathic in 2 patients. The average BMI for the cohort was 29.5. The initial 90-day complications rate for surgical intervention was 17%; with one superficial infection, one deep infection, and one death related to a cardiac event. At latest follow up 12 patients were ambulating with a CROW boot, 3 in diabetic shoes with therapeutic inserts, 1 below knee prosthesis, and 1 patient is in the initial perioperative period of healing. Radiographic union was seen in 12 patient, 3 patients had stable pseudo-union of the ankle joint with neutral alignment. Conclusion: The development of an acquired ankle deformity is associated with a poor quality of life. Traditional treatment of CA has shown to be effective when resolving infection and avoiding amputation. Our study supports the use of hindfoot nail for deformity correction/fixation and limb salvage of ankle CA patients. This patient population is highly comorbid but can have meaningful improvement in ambulator status post-surgery in a CROW boot or shoes with therapeutic insoles.